Pengaruh Terapi Kelompok Ekspresi terhadap Kualitas Hidup Pasien Skizofrenia di RSJD Dr. RM. Soedjarwadi Klaten - Rahma, Wardah Nurul; Wahyuni, Endang Sri (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Schizophrenia is a severe mental disorder that affects behavior, emotions, thoughts, and hallucinations. Schizophrenia patients often experience difficulties interacting, avoiding activities, social environments and decreased motivation, which impacts their quality of life. Art therapy within occupational therapy intervention can improve the quality of life of schizophrenia patients by helping them express their feelings and thoughts. Objectives: This study aims to determine the effect of expression group therapy on the quality of life of schizophrenia patients. Methods: Quantitative pre-experiment research (one group pretest-posttest) with sampling technique using purposive sampling based on inclusion criteria with a final total of 25 samples. Measurement of quality of life using the Indonesian version of the AQoL-4D instrument. Comparative test using paired sample t-test analysis technique with SPSS. Results: Majority of patients were aged 26-35 years (44.0%), male (60.0%), had a primary school education (36.0%), and were unmarried (44.0%). The average pretest score was 26.92, and the posttest was 21.92, with a difference of 5.00, which means there is a difference in the results of the AQoL-4D examination. The paired sample t-test results showed p value = 0.000 (p < 0.05), which means that expression group therapy affects the quality of life of schizophrenia patients. Conclusion: This study proves that there is an effect of expression group therapy on the quality of life of schizophrenia patients at RSJD Dr. RM. Soedjarwadi Klaten. Keywords : Schizophrenia, Expressive Group Therapy, Quality of Life